AB0948 TIME TO CONSIDER HYPERMOBILITY AS A CAUSE OF SYMPTOMS IN PATIENTS PRESENTING TO EARLY ARTHRITIS CLINICS: A RETROSPECTIVE ANALYSIS OF 279 PATIENTS. (2nd June 2020) - Dar, S.; Ludwig, D.; Greenwood, M.; Kazkaz, H.; Morris, V.
Abstract : Background: Joint hypermobility is a common, although largely ignored physical sign. It is often asymptomatic but can be associated with significant musculoskeletal symptoms. Joint hypermobility may also be a feature of an underlying genetic disorder and patients may present with arthralgia, recurrent soft tissue injuries and intermittent joint swelling due to mechanical instability and poor proprioception. At University College London Hospital, we run a national service for the diagnosis and management of patients with hypermobility related disorders including hypermobility spectrum disorders, Ehlers-Danlos syndromes and Marfan syndrome. Over the years we observed that a significant number of our patients had been referred to the early arthritis clinics years prior to the recognition of their hypermobility. For example, one patient with a vascular type of Ehlers-Danlos syndrome EDS (confirmed COL3A mutation) presented to 3 different hospitals over a 5-year period, with possible inflammatory arthritis prior to the EDS diagnosis. Several studies have shown that a significant proportion of patients attending early arthritis clinics do not have inflammatory rheumatic diseases. In our experience, heritable disorders of connective tissue and hypermobility spectrum disorders are often overlooked and should be included in the differential diagnosis in patients seen in the early arthritis clinics. Objectives: We aimed to audit the outcome of patients who were seen in the early arthritis clinics focusing on those who were not found to have inflammatory rheumatic diseases and to explore if joint hypermobility was considered as a possible cause of patient's symptoms. Methods: A retrospective analysis of medical records was conducted of patients attending the early arthritis clinics at University College London Hospital between May 2018 and December 2019. Results: 279 patients (90 males, 189 females) were seen in the early arthritis clinics with a mean age of 48 (range 19-91). 131 patients (47%) did not have inflammatory rheumatic diseases. Sixty-three of these patients (48%) were not given any diagnosis and joint hypermobility was not assessed during the appointment. Eleven patients (8%) had features of hypermobility, 11 patients (8%) were diagnosed with fibromyalgia, 20 patients (15%) received a diagnosis of osteoarthritis, and 27 patients (21%) were given other diagnoses including tendonitis and soft tissue pathology. Conclusion: Almost 50 % of patients who were seen in the early arthritis clinics did not have inflammatory rheumatic diseases and 21 % of patients were discharged without a clear diagnosis. In these patients, hypermobility was not assessed and this is consistent with our observation. In our experience recognising joint hypermobility as a cause of arthralgia and intermittent joint swelling usually reassures patients and motivates them to follow appropriate treatment protocols including physiotherapy and occupational therapy thus allowing a more efficient utilization of early arthritis clinic resources towards those with true inflammatory rheumatic diseases. Going forward, we have planned to embed a cognisant attitude towards hypermobility within the relevant clinics to ensure that patients who do not have inflammatory arthritis are assessed for hypermobility and directed towards appropriate management. References: [1]Castori M, Hakim A. Contemporary approach to joint hypermobility & related disorders. Current Opinion in Pediatrics. 2017;29(6):640-649. [2]Emma Connelly, Alan Hakim, Sally Davenportc & Jane Simmonds, A study exploring the prevalence of Joint Hypermobility Syndrome in patients attending a Musculoskeletal Triage Clinic. Physiotherapy Practice & Research 36 (2015) 43–53 [3]Feuchtenberger M, Nigg A, Kraus M, Schäfer A. Rate of Proven Rheumatic Diseases in a Large Collective of Referrals to an Outpatient Rheumatology Clinic under Routine Conditions. Clin Med Insights Arthritis Musculoskelet Disord. 2016; 9: 181–187. Disclosure of Interests: None declared